Nivel de percepción del visitante respecto a los servicios que presta huaca de la Luna como atractivo turístico del sector A del distrito de Moche, provincia de Trujillo, región La Libertad - Bocanegra Carbajal, Araceli Cecilia (2016)
The level of perception that visitors show regarding the services provided by the_x000D_ Huaca de la Luna Archaeological Complex is high, evidenced by tangible_x000D_ elements, reliability, responsiveness, security and empathy; Emphasizing empathy and security, according to the Likert scale with "very good", both qualifications being considered at the "High" level of perception, since in providing the service the employee offers individualized attention because human capital has previous information and Experience in the customer service generating the service is ideally performed because it serves according to the type of client (introverted, extroverted, conflictive). Also, the interest they show in the tourist attraction. At the same time there is teamwork of the different areas so as not to neglect the visitor that is given by the good working climate between the collaborators; On the other hand security is manifested with the knowledge of human capital in providing information to visitors and this is based on the selection of staff for jobs and constant training, but not all staff who are in contact with The client receives the necessary training in the English language and Moche culture._x000D_ The research used methods such as analytical-synthetic, which allowed the_x000D_ visitor's level of perception regarding Huaca de la Luna's services to be known, the ethnographic method allowed to collect data in the field and the statistical method used to collect and To elaborate the data obtained in the tourist attraction. And techniques such as the survey that was based on the SERVPERF model, technique of the interview that was performed to the contact personnel, the sampling technique and the observation technique that corroborated the reliability, responsiveness, security, empathy of the personnel Contact and tangible elements in the tourist attraction for this was used the instruments of field book, camera of photos, camcorder and observation tokens.